ADDITION TO THE FAUNA OF PSYLLID (HEMIPTERA: PSYLLOIDEA) IN POTHOHAR REGION OF PAKISTAN - M. T. Rasheed; I. Bodlah; M. F. Nasir; T. Mahmood; R. Zada; M. Asif (Journal of Animal and Plant Sciences, 2022)
Psyllid fauna of Pakistan is represented by few species only. Here, a Psyllid species: Pseudophacopteron tuberculatum (Crawford, 1912) is recorded for the first time from Pakistan. Description of immatures and adult morphology, micrographs and biology are given to validate this new faunal record and facilitate its prompt identification. Distribution map along with notes on new distributional records of four psyllid species including Acizzia indica (Heslop-Harrison, 1949); Diaphorina aegyptiaca Puton, 1892; Diaphorina citri Kuwayama, 1908 and Euphyllura pakistanica Loginova, 1973 are provided. Ecological relationship of recorded species with ants has also been given. All collected material was identified using the most relevant and available literature.
Keywords: Distribution; Immatures; New record; Pakistan